2019
DOI: 10.1016/j.jaci.2019.05.042
|View full text |Cite
|
Sign up to set email alerts
|

De novo generation of a functional human thymus from induced pluripotent stem cells

Abstract: Phillips have a patent pending for HLA-A*32:01 testing for vancomycin drug reaction and eosinophilia and systemic symptoms. S. Mallal and E. J. Phillips receive royalties from UpToDate and have equity in IIID Pty Ltd, which holds a patent for HLA-B*57:01 testing for abacavir hypersensitivity. E. J. Phillips receives consulting fees from Biocryst. The rest of the authors declare that they have no relevant conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 10 publications
0
24
1
Order By: Relevance
“…Previous studies aiming to generate thymic epithelium from PSCs showed successful differentiation from PSCs to TECs [9][10][11]26 . However, the efficiency of the TEC differentiation was generally low, and Su et al utilized a recombinant transcription factor, HOXA3, and FOXN1 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies aiming to generate thymic epithelium from PSCs showed successful differentiation from PSCs to TECs [9][10][11]26 . However, the efficiency of the TEC differentiation was generally low, and Su et al utilized a recombinant transcription factor, HOXA3, and FOXN1 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Direct reprogramming of mouse fibroblasts by enforced FOXN1 expression produced TECs capable of supporting thymocyte development in the mouse (165). In another approach, by adapting protocols which successfully differentiated human embryonic stem cells into thymic epithelium (166,167), patient-derived fibroblasts, induced to revert to a pluripotent stage of induced pluripotent stem cells (iPSCs), could be differentiated into thymic stromal progenitors (149). They could mature only upon in vivo transplantation into athymic nude mice and their capacity to fully instruct human HSC has not yet been demonstrated.…”
Section: Future Directions For Thymus Replacement Therapymentioning
confidence: 99%
“…In addition, other technologies in development, such as ESC and iPSC-derived thymii that can output functional naïve T cells, are novel tools for studying human disease etiology. As thymic epithelial cells (iPSC-TEC) (74,75) have the potential to regulate T cell production from progenitors, use of these evolving technologies in combination (gene editing and iPSC-TEC) would allow for studies to dissect how T1D-linked loci, or those linked to other diseases, regulate T cell development. These and other currently advancing technologies will greatly enhance isogenic systems, improving their capacity to model human diseases.…”
Section: Discussionmentioning
confidence: 99%